There really was a dodo - Gordon, Esther S.; Gordon, Bernard L.; Di Fiori, Lawrence (New York, H. Z. Walck, 1974)
Describes the dodo, who once flourished on the island of Mauritius, and the reasons for this large bird's extinction.
Keywords: Dodo; Dodo; Extinct animals; Birds